Lutosławski’s Worlds, red./ed. Lisa Jakelski, Nicholas Reyland. Woodbridge 2018 - Gamrat, Małgorzata (Muzyka, 2020)
Recenzja książki: Lutosławski’s Worlds, red. Lisa Jakelski, Nicholas Reyland. Woodbridge 2018